2022
DOI: 10.3390/ijerph19116357
|View full text |Cite
|
Sign up to set email alerts
|

Is Telemedicine in Primary Care a Good Option for Polish Patients with Visual Impairments Outside of a Pandemic?

Abstract: With the proliferation of telemedicine during the COVID-19 pandemic, attention began to turn to the risk of health disparities associated with its use among people with disabilities. Therefore, the present study investigates the level of interest in using teleconsultations (TCs) in primary healthcare among people with visual impairments (PVIs) and identifies their motivations and needs. A total of 219 Polish PVIs were surveyed using a combination of closed and open questions. About 50% of the respondents expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The 1688 papers considered in this analysis cover the topics shown in Figure 3 in more detail. Health professions (147), computer science (124), engineering (102), nursing (62), and social science are the most popular subjects (33). In the study, as indicated in Table 2, the three topic areas (medicine, health professions, and computer sciences) similarly had high citation rates.…”
Section: Document Year First Author Citationsmentioning
confidence: 79%
“…The 1688 papers considered in this analysis cover the topics shown in Figure 3 in more detail. Health professions (147), computer science (124), engineering (102), nursing (62), and social science are the most popular subjects (33). In the study, as indicated in Table 2, the three topic areas (medicine, health professions, and computer sciences) similarly had high citation rates.…”
Section: Document Year First Author Citationsmentioning
confidence: 79%
“…Using telerehabilitation to conduct follow-ups for newly prescribed magnifiers or other reading aids can offer another viable means for rendering vision rehabilitation services via an approach that is more convenient, safe, and resource efficient, in order to improve access to care. 6 The current findings can be used to justify and design a larger-scale noninferiority trial to determine if telerehabilitation is at least as effective as in-office usual care and that the two approaches do not result in different outcomes. This would be critical information for providers to reassure patients that either modality is acceptable.…”
Section: Discussionmentioning
confidence: 92%
“…Telerehabilitation using videoconferencing to remotely evaluate and provide visual aid training to patients with low vision at home is feasible 1 , 2 and can overcome several barriers to care 3 6 ; however, it is not yet widely implemented in clinical practice. There is a lack of a rigorous evidence basis for telerehabilitation involving magnification device training for low vision; randomized controlled trials have not yet been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…All mentioned needs have been described several times before [ 13 , 39 , 63 , 64 , 65 , 66 , 67 , 68 ]. However, they still need consideration because of existing barriers and changes regarding, inter alia, developing telemedicine [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%